Synergy of Digital Advertising Innovation in Increasing Millennial Repurchase Interest: Shopee "COD Cek Dulu" and Celebrity Endorser - Riyadi, Sugeng; Indah Sari, Yuli; Bakti, Ilham Teruna; Hapsari, Vinandri (Economics and Business Journal (ECBIS), 2024)
Compared to traditional-based advertising, innovations in digital advertising techniques by e-commerce players have now attracted repurchase interest from various generations, including millennials. Therefore, this study aims to evaluate the influence of Shopee "COD Cek Dulu" advertising and celebrity endorsers on repurchase interest, mediated by purchase decisions. Using purposive sampling, this study involved 300 millennial respondents who are Shopee “COD Cek Dulu” consumers and employed a quantitative approach based on data analysis through Smart PLS. The results revealed that Shopee "COD Cek Dulu" advertising and celebrity endorsers significantly positively affect purchase decisions. Moreover, purchase decisions have a significant positive effect on repurchase interest and were found to mediate the relationship between Shopee "COD Cek Dulu" advertising and celebrity endorsers with millennials' repurchase interest. However, while celebrity endorsers showed a significant positive effect on repurchase interest, advertising had an insignificant effect on repurchase interest.